Combination of plasma MMPs and PD-1-binding soluble PD-L1 predicts recurrence in gastric cancer and the efficacy of immune checkpoint inhibitors in non-small cell lung cancer - Ando, Fumihiko; Kashiwada, Takeru; Kuroda, Shoko; Fujii, Takenori; Takano, Ryotaro; Miyabe, Yoshishige; Kunugi, Shinobu; Sakatani, Takashi; Miyanaga, Akihiko; Asatsuma-Okumura, Tomoko; Hashiguchi, Masaaki; Kanazawa, Yoshikazu; et al. (Frontiers in Pharmacology, 2024)
The tumor microenvironment (TME) impacts the therapeutic efficacy of immune checkpoint inhibitors (ICIs). No liquid biomarkers are available to evaluate TME heterogeneity. Here, we investigated the clinical significance of PD-1-binding soluble PD-L1 (bsPD-L1) in gastric cancer (GC) patients and non-small cell lung cancer (NSCLC) patients treated with PD-1/PD-L1 blockade.We examined bsPD-L1, matrix metalloproteinases (MMPs), and IFN-γ levels in plasma samples from GC patients (n =117) prior to surgery and NSCLC patients (n =72) prior to and two months after ICI treatment. We also examined extracellular matrix (ECM) integrity, PD-L1 expression, and T cell infiltration in tumor tissues from 25 GC patients by Elastica Masson-Goldner staining and immunohistochemical staining for PD-L1 and CD3, respectively.Results: bsPD-L1 was detected in 17/117 GC patients and 16/72 NSCLC patients. bsPD-L1 showed strong or moderate correlations with plasma MMP13 or MMP3 levels, respectively, in both GC and NSCLC patients. bsPD-L1 expression in GC was associated with IFN-γ levels and intra-tumoral T cell infiltration, whereas MMP13 levels were associated with loss of ECM integrity, allowing tumor cells to access blood vessels. Plasma MMP3 and MMP13 levels were altered during ICI treatment. Combined bsPD-L1 and MMP status had higher predictive accuracy to identify two patient groups with favorable and poor prognosis than tumor PD-L1 expression: bsPD-L1 + MMP13 high in GC and bsPD-L1 + (MMP3 and MMP13) increased in NSCLC were associated with poor prognosis, whereas bsPD-L1 + MMP13 low in GC and bsPD-L1 + (MMP3 or MMP13) decreased in NSCLC were associated with favorable prognosis.Conclusions: Plasma bsPD-L1 and MMP13 levels indicate T cell response and loss of ECM integrity, respectively, in the TME. The combination of bsPD-L1 and MMPs may represent a non-invasive tool to predict recurrence in GC and the efficacy of ICIs in NSCLC.